Agroforestry and its vital role in climate change mitigation in the tropics - Razz, Rosa; León-Medina, Larry (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
The activities developed by human society cause transformations on the Earth's surface and have the capacity to affect the functioning of the planet. One of the main effects has been climate change, which affects the entirety of the planet, its ecosystems, and society. The objective of this work was to carry out a bibliographic review through the compilation of scientific articles, book chapters, and reviews from reliable documentary sources. The review focused on the factors that influence climate change and its consequences. Additionally, this work presents an alternative: the implementation and use of agroforestry systems to mitigate climate change. This is not only because of their potential to capture and store carbon but also to reduce the amount of CO2 in the atmosphere through the growth of trees and shrubs. Agroforestry systems also have significant implications for sustainable development due to the social, economic, and environmental benefits they provide.